The effect of subsidized employment on happiness - Crost, Benjamin (Berlin, 2011)
"While a large body of evidence suggests that unemployment and self-reported happiness are negatively correlated, it is not clear whether this reflects a causal effect of unemployment on happiness and whether subsidized employment can increase the happiness of the unemployed. To close this gap, this paper estimates the causal effect of a type of subsidized employment projects - Germany's Arbeitsbeschaffungsmaßnahmen - on self-reported happiness. Results from matching and fixed effects estimators suggest that subsidized employment has a large and statistically significant positive effect on the happiness of individuals who would otherwise have been unemployed. Detailed panel data on pre- and post-project happiness suggests that this effect can neither be explained by self-selection of happier individuals into employment nor by the higher incomes of the employed."